Solar Thermal Collectors for Medium Temperature Applications: A Comprehensive Review and Updated Database. (June 2016) - Iparraguirre, Iñigo; Huidobro, Ana; Fernández-García, Aránzazu; Valenzuela, Loreto; Horta, Pedro; Sallaberry, Fabienne; Osório, Tiago; Sanz, Asier
Abstract: Although the technology of solar thermal collectors for medium temperature applications is not new, few collectors and commercial installations were available worldwide. Presently the sector is growing rapidly, new technologies have been developed and real installations using these technologies are already being built all around the world for different applications, especially for the generation of heat required by industrial applications. Considering the increasing number of available products and the importance of disseminating this information among system designers and end-users, a database of the available solar collectors for medium temperature applications is under development. The information has been gathered from the different collector manufacturers and suppliers and the available technical information published on the different collector models. Aiming a thorough insight into these new commercially available solutions, the database includes the most relevant technical information of the different existing collectors. This work is being done within the framework of the European project STAGE-STE (Scientific and Technological Alliance for Guaranteeing the European Excellence in Concentrating Solar Thermal Energy) (http://www.stage-ste.eu/ ). The information gathered will also be used within the Task 49, the working group for Solar Heat Integration in Industrial Process (SHIP) of the Solar Heating and Cooling program (SHC) by the International Energy Agency (IEA) (http://task49.iea-shc.org/).